Bond tests to evaluate the effectiveness of anchoring devices for CFRP sheets epoxy bonded over masonry elements. (15th March 2017) - Ceroni, Francesca
Abstract: The effectiveness of Fiber Reinforced Polymer (FRP) materials for external strengthening of existing masonry elements is strictly conditioned by debonding phenomena. To avoid or delay the debonding and, hence, attain higher failure loads or larger ductility at failure, end anchoring devices may be a very suitable solution. Several types of end anchoring devices have been proposed, especially for concrete elements, but for none of them design indications for predicting the increase in failure load have been suggested so far. This paper is firstly aimed to provide an overview of the most diffuse and efficient anchoring techniques and quantify their efficiency in terms of failure load increase. Then, it presents the results of a wide experimental program carried out by the author and concerning bond tests on masonry elements externally bonded with Carbon FRP sheets and provided of different types of end anchoring devices. The bond tests have been realized according to a single pull-push set-up. Single stones made of yellow tuff and prisms made of clay bricks were used as support for the bond tests. The experimental results have been examined in terms of debonding load, load-slips curves, distribution of axial strains and bond shear stress-slip relations in order to highlight the effectiveness of the different tested anchoring systems on both the local bond behavior and the global performance. Finally, some design indications are also provided basing on both the experimental results herein presented and literature data concerning similar anchoring systems.